Aprendizagem Baseada em Projeto simulando o Método de Design Sprint: “5 dias” em um Semestre - Silva Prietch, Soraia; Langstton Costa Alves, Mickael (Anais Estendidos do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2018: Anais Estendidos do XVII Simpósio Brasileiro sobre Fatores Humanos em Sistemas ComputacionaisDO - 10.5753/ihc.2018.4208, 2018)
The goal of this paper is to present a brief report of the Human-Machine Interface course’ conduction, techniques used and some results delivered by students. The theme of application during the semester was “Engaged Communities”, according to the Call for Design Competition for Students of CHI’18. From competition’s instructions, we simulated Design Sprint sections, during one semester, as a strategy to organize design proposals and learning assessment.